Ethics of Medical Assistance in Dying for Non-Terminal Illness: A Comparison of Mental and Physical Illness in Canada and Europe - Birkness, Katharine; Rudnick, Abraham (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
Medical assistance in dying (MAiD) is scheduled to be legalized in Canada as of March 2024 for individuals with mental disorder/illness as their sole underlying medical condition (MAiD MD-SUMC). As guidelines are being developed for the safe and consistent provision of MAiD MD-SUMC, sufficient consideration must be given to the interpretation of ambiguous terminology in current legislation, and to ensuring sound use of acceptable ethics principles in these interpretations.